Conceptual structure representation of causative verb in Malay language and relation with syntax [Representasi argumen struktur konseptual bagi kata kerja kausatif Bahasa Melayu dan hubungannya dengan sintaksis] - Yusof,, Maslida; Rosly, Nurul Jamilah (Universiti Kebangsaan Malaysia Press, 2019)
Causative verbs can refer to an act because of something that is happening, because nothing will happen without any specific reason, for the occurrence of a favor and the reason for to justifying something. Therefore, this study will examine lexical verbs that are causative in representing the structure of the argument and its relation to syntax. To examine the lexical verb of causative in representing the structure of the argument and its relation to the syntax, this study will focus on the lexical of verb kill, force, allowed and help from the organizational class of the conceptual structure of semantics using data taken from the Corpus Base of the Dewan Bahasa dan Pustaka as an example of a data. The analysis of the study will use the Conceptual Structure Theory – by Ray Jackendoff (2011). Semanticrepresentations are depicted in the form of conceptual structures within the Function [Event] that carry the conceptual structure of the formula [Event CAUSE ([THING, x], [Event ([y], [x])])]. The findings show the representation of conceptual structures for verbs to kill, force, allowed and help represented by constituents [Event CAUSE ([BE X], [Y])]), NO [event LET ([ GO X], [Y])], and [Event HELP ([ GO X], [Y])] to constituents [THING], [PLACE] and [PATH]. For conceptual structure representation to syntax, data findings indicate a connection between the Head Rules and Arguments Rules based on the role of the argument being a subset of the acceptance and verbal request to the Name Phrase. Consequently, this study will show the representation of conceptual structure and its relationship with systematic syntax and especially in the verbal nature.